In Tribute to Robert Robinson Brubaker (1933–2025) - V. L. Motin; V. V. Kutyrev (Проблемы особо опасных инфекций, 2025)
The article is dedicated to the famous scientist-plague specialist Robert Robinson Brubaker. The contribution of R. Brubaker to the study of the plague microbe, his main scientific achievements, as well as his merits as a researcher, teacher, mentor are noted.